Enhancement of the fatigue life of recycled PP by incorporation of recycled opaque PET collected from household milk bottle wastes. (15th April 2021) - Tramis, O.; Garnier, C.; Yus, C.; Irusta, S.; Chabert, F.
Highlights: Recycled opaque PET (rPET-O) acts as a reinforcement (filler) for the rPP. Improvements in tensile-tensile fatigue life are seen for rPET-O/rPP blends. rPET-O shifts the fatigue damaging of blends from fatigue to quasi-static damaging. Blending rPET-O with rPP may be a new route to recycle opaque PET without sorting. Abstract: Opaque PET (Polyethylene terephthalate) was recently introduced as a dairy packaging, mainly for milk bottles. Opaque PET, obtained as PET filled with mineral nanoparticles, allows for a reduction of bottles' thickness, thus a cost reduction for industrials. For this reason, the use of opaque PET is steadily increasing. However, its recyclability is nowadays an issue: although the recycling channels are well established for transparent PET, the presence of opaque PET in the household wastes weakens the existing recycling channels. Besides, many initiatives are launched in Europe to turn wastes into resources, as one key to a more circular economy. One of the biggest challenges is an efficient sorting of the plastic solid wastes since the PET is not miscible with other plastics such as polypropylene (PP) from the bottle caps and polyethylene (PE) from the other milk bottles. In this work, the mechanical properties of uncompatibilized blends of opaque PET (rPET-O) with recycled polypropylene (rPP) have been studied; both are collected from household wastes. The tensile properties and the fatigue life of rPP, monitored by in-situ digital image correlation and in-situ infrared thermography, are increased by the incorporation of rPET-O. rPET-O/rPP blends may be substituted to rPP for similar applications, with no need to sort the caps from the bottles. Thus, as a concept, the incorporation of opaque PET into the PP recycling sector may be a new route to absorb some of the growing amounts of opaque PET.